Some findings from further exploration of the “composite good” approach to contingent valuation (2017)
In this chapter, we report on some components of a larger study addressing “budget awareness” considerations in contingent valuation (“CVM”) studies. The study explored general population willingness to pay (“WTP”) for essentially the same environmental resource under several different budget awareness approaches, using a split-sample design. In the fall of 2014 (after substantial development work), we undertook a survey with a total achieved sample size of almost 4,000 households. This chapter reports two of those approaches, based on subsamples totaling approximately 2,400 households: the use of within-questionnaire “wording additions” and the disaggregation of a value obtained for a larger composite good.